Jednostka w systemie bezpieczeństwa powszechnego – zagadnienia wybrane - Mielczarek-Mikołajów, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego. Wydawnictwo "Szermierz" sp. z o.o., 2023)
The concept of general security is understood as a condition in society that conditions its proper functioning and is aimed at the protection of such values as, inter alia, life, health, property of citizens, political system or state sovereignty. Tasks in this area are performed primarily by public administration bodies. It should be noted, however, that the protection of these values is also the responsibility of the individual. Due to this, the author will draw attention to selected provisions of the Constitution of the Republic of Poland on the 2 of April of 1997 and certain acts, as well as the need to shape a safety culture among the society.
Keywords: universal safety; individual; public safety; public task